Effects of Exposure to Incense Smoke Associated with Impaired Lung Function and Respiratory Disease: A Systematic Review - Mertha Adnyana, I Made Dwi; Utomo, Budi; Dewanti, Linda; Fauziyah, Shifa; Eljatin, Dwinka Syafira; Setyawan, Muhamad Frendy; Sumah, Lesty Helda Marsel; Karina, Citra Al (National Journal of Community Medicine, 2023)
The community uses incense (bakhour) through ceremonies, traditional health practices, and aromatherapy. Nevertheless, evidence from experiments and studies of populations suggests that a habit of burning incense makes the lungs work less well. The study investigated the relationship between exposure to incense smoke and impaired lung function and respiratory diseases. Data tracing was carried out systematically following PRISMA guidelines from January to April 2022 and registered in the PROSPERO database. The articles selected in this review were cross-sectional, cohort, observational, and experimental studies based on the criteria: (1) animals or humans exposed to incense smoke; (2) exposure to incense smoke which was carried out indoors or outdoors; (3) the selected articles which were included in the original type of article; (4) the publication year between 2016-2021 and the selected articles entered into reputable journals (Scopus and Web of Science). JBI guidelines and synthesis guidelines without meta-analysis (SWiM) to determine the level of evidence and minimize bias and interpretation of results. This study describes respiratory symptoms or diseases, home use of incense, and lung function measurement. Six articles were included; 6 (100%) reported using incense indoors, and 5 (83%) reported using incense outside the home. Respiratory symptoms and diseases caused by exposure to incense sticks are 5 (83%) shortness of breath, 6 (100%) wheezing, asthma, and inflammation of the lungs, 2 (33%) chronic obstructive pulmonary disease, and 4 (67%) allergic rhinitis. Incense smoke particles decrease lung function based on FVC, FEV, PEFR, and FEF values of 25-75%. The results indicate that smoking incense adversely affects lung function and leads to respiratory diseases. The community and related parties can minimize and conduct education and prevention related to simultaneous incense exposure in the community to reduce the burden of diseases and disorders due to respiratory incense smoke in areas that use it daily.